Myths and ceremonies in schools: Analysis of school projects in terms of new institutional theory - Salih Arslan; Hakkı Kahveci (Social Sciences and Humanities Open, 2025)
The primary purpose of this study is to examine the rationale and the process of carrying out projects in public schools in Türkiye from the perspective of New Institutional Theory (NIT). A multiple-case study design was adopted, and data were collected via semi-structured interviews with 19 teachers involved in eTwinning, TÜBİTAK, or Erasmus + projects. The data were analysed through thematic analysis. The findings indicate that projects are often carried out for coercive reasons, such as administrative pressure and the pursuit of personal gain, as well as for cognitive reasons, such as the belief that project work is beneficial. It was also found that projects have become institutional myths and are carried out ceremoniously. This points to the loose coupling between project outcomes and school goals. This loose coupling means that project activities are not primarily driven by educational quality concerns. This study's distinctive aspect is its use of a theoretical lens to reveal the institutional background of school projects.